How far is a long distance? An assessment of the issue of scale in the relationship between limiting long‐term illness and long‐distance migration in England and Wales. Issue 2 (30th August 2017) - Wilding, Sam; Martin, David; Moon, Graham
Abstract: Research consistently shows that those in poor health are less likely to migrate over long distances, but analyses rarely consider what constitutes a long distance in this context. Additionally, the migration literature often fails to account for place of residence effects on migration behaviour. This paper addresses these issues through analysis of the distance of residential moves by working age adults in the year preceding the 2011 Census. Multilevel logistic regression models predict the odds of having moved long‐distance relative to short distance, for different definitions of long distance: ≥10 km, ≥20 km and ≥50 km. We test whether those reporting a limiting long‐term illness (LLTI) are less likely to move long distance in all models, controlling for local authority at the time of the 2011 Census. We find no evidence for health selection in long‐distance migration in the 10 and 20 km models, but uncover a significant effect in the 50 km model. By age, the odds of having moved long distance do not vary for middle‐working age adults (25–54) by LLTI, whereas those with an LLTI in the pre‐retirement age group (55–64) are less likely to move long distance in all models. We uncover clusters of local authorities where those with an LLTI are more likely to have moved long distance in the 10 and 20 km models, but in the 50 km model, only two of these areas remain significantly positive. We conclude that health selection in distances moved occurs above a cut‐off somewhere between 20 and 50 km.